Smartphone app uses loyalty point incentives and push notifications to encourage influenza vaccine uptake. Issue 32 (26th July 2019) - Dale, Leila Pfaeffli; White, Lauren; Mitchell, Marc; Faulkner, Guy
Highlights: Carrot Rewards is a free, incentive-based, smartphone health app available in participating Canadian provinces. An in-app quiz educated users about the importance of the influenza vaccine and promoted pharmacy influenza clinics. The app used novel "push" notifications when the user was within 200 m of the sponsored pharmacy. The quiz completion rate was high although only a small number visited the pharmacy. Loyalty point incentives did not appear to influence pharmacy visits. Abstract: Purpose: Carrot Rewards is a free, incentive-based, smartphone health app available in participating provinces in Canada. One feature of Carrot was designed to incentivize influenza vaccine education messages and encourage vaccine uptake for users in the province of British Columbia. This study aimed to evaluate the uptake of the Carrot Flu Campaign educational quiz and to determine if mobile "push" notifications, plus loyalty point incentives, resulted in users visiting a sponsored pharmacy to discuss and receive the influenza vaccine. Methods: The Carrot Flu Campaign delivered an in-app quiz, educating users on the importance of the influenza vaccine. Push notifications were then sent to users when they came within 200 m of a sponsored pharmacy. Those who visited the pharmacy collected bonus points and completed a follow up quiz tracking influenza vaccine behaviour. A sub-sample of users completed the Flu Campaign between their baseline and follow up Health Risk Assessment (HRA), a survey which asked about influenza vaccine uptake behaviour. Descriptive statistics were summarized. Results: A total of 38.1% (30, 538/80, 228) registered Carrot users completed the Flu Campaign quiz. Of those in participating cities (n = 21, 469), 41% clicked on the map to show the nearest sponsored pharmacy and 78% enabled their smartphone's "locations" feature, allowing them to receive the push notifications. A small number of users spoke to a pharmacist (n = 96) and less than half reported receiving the influenza vaccine (38/96; 39.6%). From the HRA sub-sample (n = 3693), approximately 5% more users reported receiving the influenza vaccine during the 2017 influenza season compared to the previous year. Conclusions: Carrot Rewards used a novel delivery method to educate the general population and showed geolocation could be used to facilitate influenza vaccine uptake. Future iterations could tailor content to target those most at risk and should consider more robust evaluation methods to determine the app's effectiveness.